2011
DOI: 10.1093/ecam/neq006
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐Oxidative Abilities of Essential Oils from Atractylodes ovata Rhizome

Abstract: The rhizome of Atractylodes ovata De Candolle is rich in essential oils, which are usually removed by processing. In this study, anti-oxidative abilities of essential oils and aqueous extracts of A. ovata rhizome were explored, and the influence of processing on the anti-oxidative abilities was examined. Essential oils and aqueous extracts of A. ovata were extracted by boiling water and steam distillation, respectively. Quality of these two A. ovata samples was controlled by HPLC and GC-MS system, and anti-oxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 39 publications
(32 reference statements)
0
19
0
Order By: Relevance
“…Accordingly, it is conceivable that antioxidants might play an important role in protecting the intestinal barrier against LPS insult. Substantial evidence has demonstrated the antioxidant activities of plants and herbs [49, 50], including RAM [23, 24]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, it is conceivable that antioxidants might play an important role in protecting the intestinal barrier against LPS insult. Substantial evidence has demonstrated the antioxidant activities of plants and herbs [49, 50], including RAM [23, 24]. …”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have shown that many plant and herbal extracts and their products, such as polyphenolic substances (e.g., flavonoids and tannins), exert potent antioxidant actions. RAM, an herb utilized in various dietary preparations in Asian countries, has been reported to possess antioxidant activities [23, 24]. It has been shown that RAM prevents viral gastroenteritis via the protection of intestinal mucosal cells against injury and improvement in the absorptive function [25].…”
Section: Introductionmentioning
confidence: 99%
“…DJS consists of 6 herbs and each herb also has antioxidant effects [3337]. We hypothesize that antioxidant effects are responsible for the results from above antithrombotic studies.…”
Section: Discussionmentioning
confidence: 99%
“…The cinnamaldehyde present in Ramulus Cinnamomi significantly reduces the peroxidation of lipids and the amount of GSH by inhibition of the enzymatic activities of superoxide dismutase and by upregulation of the expression of Nrf2 [57, 58]. The atractylon in Atractylodes macrocephala Koidz was reported to have strong antioxidative abilities [59, 60]. The Paeoniflorin in Radix Paeoniae Alba targets the Nrf2/ARE signal pathway to inhibit the oxidative stress in the high-glucose-induced Schwann cells by reduction of the amounts of ROS and MDA and by the increased expressions of GST and GPX [61].…”
Section: Discussionmentioning
confidence: 99%